2011
DOI: 10.1080/09084282.2011.595451
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Depression and Alzheimer's Disease Using the Cattell-Horn-Carroll Theory

Abstract: Clinical differentiation between Alzheimer's disease (AD) and depression is often difficult due to symptom overlap and similar clinical presentation. Concise and accurate diagnostic tests have been of interest for many years. Furthermore, with the continued growth of the Cattell-Horn-Carroll (CHC) theory, there has been an emergence of measures such as the Woodcock-Johnson-III Tests of Cognitive Abilities (WJ-III COG), which are being more commonly used in clinical practice yet have not been fully evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
(70 reference statements)
0
5
0
1
Order By: Relevance
“…To draw a coherent and valid comparison between them, each neuropsychological test was classified under one of the cognitive factors of the Cattell-Horn-Carroll (CHC) model [15]. This model has been used in other metaanalyses of epilepsy [16] and as a conceptual framework in other pathologies [17][18][19][20]. The tests used in the selected studies were classified under six of the CHC model's broad stratum abilities: general cognitive ability (G), comprehensive knowledge (Gc), fluid reasoning (Gf), long-term memory (Glr), cognitive processing speed (Gs), and span and working memory (Gsm).…”
Section: Summary Measures and Calculation Of Effect Sizementioning
confidence: 99%
“…To draw a coherent and valid comparison between them, each neuropsychological test was classified under one of the cognitive factors of the Cattell-Horn-Carroll (CHC) model [15]. This model has been used in other metaanalyses of epilepsy [16] and as a conceptual framework in other pathologies [17][18][19][20]. The tests used in the selected studies were classified under six of the CHC model's broad stratum abilities: general cognitive ability (G), comprehensive knowledge (Gc), fluid reasoning (Gf), long-term memory (Glr), cognitive processing speed (Gs), and span and working memory (Gsm).…”
Section: Summary Measures and Calculation Of Effect Sizementioning
confidence: 99%
“…They are not surprising and consistent with previous studies reported that memory tasks have relatively high power to discriminate AD and older depressed patients. However, these studies have focused on a single or overall cognitive composite score and were carried out in small samples size which could result in a probable lack of statistical power (Swainson et al, 2001 ; Foldi et al, 2003 ; Künig et al, 2006 ; Dierckx et al, 2007 , 2011 ; Federico et al, 2008 ; Contador et al, 2010 ; Para et al, 2010 ; Croisile et al, 2011 ; Mazur-Mosiewicz et al, 2011 ; Rotomskis et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This point is relevant since LLD patients with poor memory performance have an increased risk of developing AD (Diniz et al, 2013 ; Kaup et al, 2016 ). It is an important challenge in psychiatry and neurology (Künig et al, 2006 ; Leyhe et al, 2017 ; Liguori et al, 2018 ) from a prognostic and therapeutic point of view (Birrer and Verumi, 2004 ; Mazur-Mosiewicz et al, 2011 ; Rotomskis et al, 2015 ; Gasser et al, 2018 ). However, future longitudinal research should consider estimating whether the base rates analyzing low memory scores by using different cut-offs, could have a useful predictive value for people with LLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studier indikerer at tester som setter krav til laering (33), benevning og kompleks visuokonstruktiv evne kan skille depresjon fra demens av Alzheimers type (29,34). Det har videre vaert funnet at pasienter med demens av Alzheimers type gjør det signifikant svakere enn deprimerte ved intellektuell evnetesting (målt ved matriseresonnering, en test som måler evnen til logisk resonnering, abstrakt tenking og problemløsningsevne) (29,35,36). Demens av Alzheimers type medfører altså en reduksjon i intellektuelt evnenivå over få år, i motsetning til det som skjer ved en depresjon (14).…”
Section: Nevropsykologiske Testerunclassified